Message - Rao, Dr. U. S. Mahadeva (Universal Journal of Pharmaceutical Research, 2024)
Fraternal Greetings! For the researchers, the select of the appropriate journal to propagate their research outcomes is vivacious to their accomplishment. This is principally imperative if new findings and data need to be dispersed in fast track which is need of the hour for a researcher. Research findings depend on original flawless thinking and broadcasting of the research aftermaths. UJPR paves way for scientific dissemination of research outcomes in comprehensive areas such as pharmaceuticals, nutraceuticals, cosmeceuticals, biosciences, chemo-informatics, biomedical informatics, etc. UJPR is an international journal emerging to pinnacle in a shorter span of period with the backing of vigorous review process that meet global standards. Of course, the journal has illustrious editorial and eminent review board members with weighty experience in their area of expertise. It is indexed in not less than 40+ indexing services and sooner expected to gain SCOPUS index. I propose researchers to consider this journal as one of their choice to publish their findings. The Chief Editor constantly appreciate editors and reviewers for their persistence and hard work and likewise welcome any comments and suggestions to improve the quality of the journal.